Perencanaan Pembelajaran PAI Berbasis Media Visual Bagi Anak Tuna Rungu - Guntur Cahyono (Institut Agama Islam Negeri Palopo, 2019)
This research aims to describe the learning characteristics of Islamic education toward hearing impaired students, and present the challenges in the learning process to find solutions. As a descriptive research, it reveals the learning needs for hearing impaired students at SMA-LB Wantuwirawan Salatiga. The use of media on the basis of visual is expected to be the initial solution to vary learning models for the students who have a hearing problem. Thus, teachers should make learning plans on the basis of visual as the main sense of hearing impaired students.